QLTI-07. IDENTIFYING RISK FACTORS FOR PROLONGED TRANSFUSION-DEPENDENT TEMOZOLOMIDE-INDUCED THROMBOCYTOPAENIA IN PATIENTS RECEIVING CONCURRENT CHEMO-RADIOTHERAPY FOR GLIOBLASTOMA (GBM). (14th November 2022) - Ismail, Nashwah; Patel, Karan; Parikh, Tapan; Colaco, Rovel; McBain, Catherine
Abstract: BACKGROUND: Temozolomide-induced thrombocytopaenia is a well-recognised clinical issue with significant inter-patient variation. However, knowledge of the extent of the problem and its potential risk factors remains limited. Our aim was to determine the incidence of patients requiring platelet transfusion and ascertain associated risk factors using real-world data. METHODS: Data from patients with GBM receiving concurrent temozolomide-chemo-radiotherapy (CRT) from 01/01/18-31/12/2019 retrospectively reviewed. Patients receiving platelet transfusion identified (Local policy: transfusion for platelet count ≤ 30x10 9 /L). Logistic regression and chi-squared tests used to compare variables in patients requiring platelet transfusion and those not. RESULTS: 111 patients with GBM received TMZ-CRT (60Gy/30#; 75mg/m 2 temozolomide). 12/111 patients received platelet transfusion: 10 during concurrent-CRT and 2 during adjuvant-treatment. Numbers of transfusions: 1-2: 7 patients; 3-4: 2 patients; ≥ 5 transfusions: 3 patients. Median time from platelet count ≥ G3 to ≥ 100 in 11/12 patients: 38 days (range 6-72). 1 did not recover, patient died 84 days following start of TMZ-CRT with thrombocytopaenia. Comparison of the transfused vs the non-transfused cohort shows: transfused: 50% female; non-transfused: 36% female. Mean BSA: transfused: 1.73, SD0.21; non-transfused:1.96, SD0.22 (OR 0.01; 95% CI:0.0003 – 0.16). Mean age: transfused: 57, SD15.8; non-transfused: 58, SD10.7 . Mean baseline platelet count: transfused: 329, SD185; non-transfused: 319, SD117. Mean PTV: transfused: 400, SD115; non-transfused: 414, SD123. There were no statistically significant associations with demographics, age, blood parameters or planning target volume. CONCLUSION: This study demonstrates a subset of patients who experience severe and prolonged thrombocytopaenia. Risk factors elucidated are female sex and lower BSA. Large-scale prospective trials evaluating a panel of predictors including concomitant medications, patient MGMT variants and temozolomide-metabolite concentrations would be valuable. Precise stratification of this vulnerable subgroup may permit consideration of temozolomide dose-capping in the future. Careful informed consent with all patients and caution with intensifying treatment under trials is vital presently.